Analysis of the changes of income tax provision on goods and services related to gold - Pusparini, Putu Dian; Budiarsih, Riani (Educoretax, 2024)
One of the economic transactions that has become a potential taxation for the Directorate General of Taxes (DGT) is gold, where its Income Tax- Withholding are regulated in the Regulation of Finance Minister (PMK). As of May 1, 2023, Income Tax Article 22 on transactions related to gold has changed through the issuance of PMK Number 48 Year 2023. There is a decrease in the Income Tax Article 22 rate from 0.45% to 0.25% and an expansion of the taxation base which was originally only on gold bullion, now extends to gold jewelry and jewelry made of other than gold. This study aims to determine the factors behind and the impact of the issuance of this PMK. The method used in this research is qualitative through interviews with policy makers at the DGT and literature study. The results show that some of the factors that support the issuance of this regulation are due to: the unique characteristics of gold; the absence of special regulations for gold; the need for legal certainty, justice, convenience and simplicity of tax imposition; and the need to encourage business actors to contribute actively. The issuance of this PMK has an impact on optimizing state revenue.